ifo World Economic Survey May 2017 - Dorine Boumans (ifo World Economic Survey, 2017)
World Economic Climate: ifo World Economic Climate Improves Markedly - Advanced Economies: Advanced Economies keep their Momentum - Emerging and Developing Economies: Emerging and Developing Economies show Signs of a Cautious Recovery - Special Topic: The WES Special Question: The Economic Effects of Populism
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies